Indigenous Knowledge: Inclusive Environmental Communication - Pranidhi, Dharmika; Beliatte, Metteyya (Faculty of Communication Science | Universitas Pancasila Jakarta, Indonesia, 2025)
This comprehensive article explores the indispensable role of Indigenous Knowledge (IK) in fostering truly inclusive environmental communication, particularly in the face of escalating global climate challenges. Drawing upon a synthesis of existing literature and real-world case studies, this paper elucidates how Traditional Ecological Knowledge (TEK)—a profound, place-based understanding of environmental stewardship—offers critical insights often overlooked in conventional environmental discourse. It highlights the historical marginalization of IK and advocates for a paradigm shift towards communication approaches that are culturally responsive, participatory, and equitable. The Inclusive Environmental Communication Framework (IECF), consisting of four interdependent domains, is proposed as a holistic and operational solution to guide inclusive environmental communication. The findings underscore that ethical and meaningful incorporation of Indigenous perspectives not only enriches environmental dialogue but is fundamental for achieving more effective, just, and sustainable climate action globally.